Whole-Organ analysis of calcium behaviour in the developing pistil of olive (Olea europaea L.) as a tool for the determination of key events in sexual plant reproduction - Zienkiewicz Krzysztof; Rejón Juan D; Suárez Cynthia; Castro Antonio J; de Dios Alché Juan; Rodríguez García María (BMC Plant Biology, 2011)
Abstract Background The pistil is a place where multiple interactions between cells of different types, origin, and function occur. Ca2+ is one of the key signal molecules in plants and animals. Despite the numerous studies on Ca2+ signalling during pollen-pistil interactions, which constitute one of the main topics of plant physiology, studies on Ca2+ dynamics in the pistil during flower formation are scarce. The purpose of this study was to analyze the contents and in situ localization of Ca2+ at the whole-organ level in the pistil of olive during the whole course of flower development. Results The obtained results showed significant changes in Ca2+ levels and distribution during olive pistil development. In the flower buds, the lowest levels of detectable Ca2+ were observed. As flower development proceeded, the Ca2+ amount in the pistil successively increased and reached the highest levels just after anther dehiscence. When the anthers and petals fell down a dramatic but not complete drop in calcium contents occurred in all pistil parts. In situ Ca2+ localization showed a gradual accumulation on the stigma, and further expansion toward the style and the ovary after anther dehiscence. At the post-anthesis phase, the Ca2+ signal on the stigmatic surface decreased, but in the ovary a specific accumulation of calcium was observed only in one of the four ovules. Ultrastructural localization confirmed the presence of Ca2+ in the intracellular matrix and in the exudate secreted by stigmatic papillae. Conclusions This is the first report to analyze calcium in the olive pistil during its development. According to our results in situ calcium localization by Fluo-3 AM injection is an effective tool to follow the pistil maturity degree and the spatial organization of calcium-dependent events of sexual reproduction occurring in developing pistil of angiosperms. The progressive increase of the Ca2+ pool during olive pistil development shown by us reflects the degree of pistil maturity. Ca2+ distribution at flower anthesis reflects the spatio-functional relationship of calcium with pollen-stigma interaction, progamic phase, fertilization and stigma senescence.